2008
DOI: 10.1016/s0004-9514(08)70067-9
|View full text |Cite
|
Sign up to set email alerts
|

Severe other joint disease and obesity independently influence recovery after joint replacement surgery: an observational study

Abstract: Severe other joint disease and obesity are associated with poorer recovery after surgery. Clinician and patient expectations, rehabilitation, and benchmarking can be guided by these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
47
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 23 publications
4
47
1
Order By: Relevance
“…Several recent studies [9,10,14,27] have examined the impact of obesity on function of TKA (Table 5). Although some authors reported no differences in the function between nonobese and obese patients during short-term and long-term followups [9,27], others have reported that severely obese patients had poorer function [10,18]. Unlike Spicer et al [24] who reported poorer preoperative scores with obese patients, our patients had similar preoperative outcome scores, the only exception being that the severely obese patients had poorer ROM.…”
Section: Discussioncontrasting
confidence: 45%
“…Several recent studies [9,10,14,27] have examined the impact of obesity on function of TKA (Table 5). Although some authors reported no differences in the function between nonobese and obese patients during short-term and long-term followups [9,27], others have reported that severely obese patients had poorer function [10,18]. Unlike Spicer et al [24] who reported poorer preoperative scores with obese patients, our patients had similar preoperative outcome scores, the only exception being that the severely obese patients had poorer ROM.…”
Section: Discussioncontrasting
confidence: 45%
“…Obesity is associated with poor short-term locomotor outcome following a TKR (13,14). Naylor et al evaluated mobility recovery within 1 year post-TKR and observed that obese patients walked more slowly during the 15-meter walk test and required more time to complete the TUG test compared with nonobese patients at 12 weeks and 26 weeks post-TKR (14).…”
Section: Discussionmentioning
confidence: 99%
“…Naylor et al evaluated mobility recovery within 1 year post-TKR and observed that obese patients walked more slowly during the 15-meter walk test and required more time to complete the TUG test compared with nonobese patients at 12 weeks and 26 weeks post-TKR (14). J€ arvenp€ a€ a et al showed that obesity was associated with poorer recovery in knee range of motion and reported that obese patients presented with more pain at 3 months post-TKR compared with nonobese patients (13).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations